Strategi Komunikasi Organisasi Dalam Meningkatkan Kinerja BPH di MRadio FISIP UMJ - Wadkhulli Jannati Priyoko; Rivan Rio Saputra; Andika Arief Rachman Suharyadi; Theofanny; Jamiati, Jamiati (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This research was conducted to find out the organizational communication strategy in MRadio. This research used qualitative method by interviewing the Station Manager of MRadio. Qualitative method is a method that emphasized descriptive or analytical, qualitative method is a subject perspective that is highly emphasized and the theory base used by researchers as a guide that aims for a research process that is in accordance with field facts. The results of this study use behavioral communication theory to improve the performance of MRadio’S BPH is very important in doing work, reducing conflict, understanding organizational goals, can improve communication skills to improve the quality that exists in organization